2017
DOI: 10.3892/ol.2017.7596
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the L1 gene and integration of human papillomavirus 16 and 18 in cervical carcinoma and premalignant lesions

Abstract: High-risk human papillomavirus (HPV) is the primary cause of cervical carcinoma (CC). Viral integration into the host chromosomes is associated with neoplastic progression, and epigenetic changes may occur as a result. The objective of the present study was to analyze HPV L1 gene methylation and to compare the use of quantitative polymerase chain reaction (qPCR), in situ hybridization (ISH) and L1 methylation analysis as methods for detecting HPV integration. Cervical scrapes or biopsy samples positive for HPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Host or viral epigenetic changes may be enhanced by the integration of HPV. A recent study showed that L1 gene methylation increases significantly according to the grade of the cervical lesion, and a high methylation rate of this gene correlates with the physical status of HPV integration (66, 67).…”
Section: Natural History Of Mucosal Hpv Infectionsmentioning
confidence: 99%
“…Host or viral epigenetic changes may be enhanced by the integration of HPV. A recent study showed that L1 gene methylation increases significantly according to the grade of the cervical lesion, and a high methylation rate of this gene correlates with the physical status of HPV integration (66, 67).…”
Section: Natural History Of Mucosal Hpv Infectionsmentioning
confidence: 99%
“…These results suggest that ISH has good concordance with qPCR with regards to the detection of HPV integration. Therefore, this method can be used for determining the physical status of HPV (41). The present study identified that women with LSIL (60%), with HSIL (65%) and with SCC (10%) had principally a mixed state.…”
Section: Discussionmentioning
confidence: 69%
“…It is important to note that in LSIL the number of altered cells is lower compared with HSIL. In addition, it has been reported that viral integration in SIL and CC is more frequently related to HPV16, 18 and 58 genotypes (41,46).…”
Section: Discussionmentioning
confidence: 99%
“…The L1 region of HPV is susceptible to DNA methylation which, interestingly, has been associated with lesion grade and viral integration. For example, methylation of CpG 5698 and 5617 is associated with high-grade lesions and CC ( Turan et al, 2006 ; Buck et al, 2013 ; Wang and Roden 2013 ; Torres-Rojas et al, 2018 ).…”
Section: Structure and Function Of Human Papillomavirus Genomementioning
confidence: 99%